Rovdjursproblematik i Sverige med fokus på varg och får. Vilka lösningar finns? - Andersson, Sofia (2013)
The Swedish wolf population is like continue to grow and this will eventually lead to an increase in the predation of livestock. In Sweden carnivore attacks happen most frequent on sheep farms and the majority of these attacks are performed by wolves. Because of this, the main focus in this study is on the sheep and wolf problematic.